2013
DOI: 10.1002/cvde.201207044
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Source Precursor‐Based Deposition of Sb2Te3 Films by MOCVD**

Abstract: The low-temperature metal-organic (MO)CVD of Sb 2 Te 3 films is achieved by the use of the single-source precursor (Et 2 Sb) 2 Te, 1. The role of the substrate temperature on the deposition rate and the composition of the resulting film is described. The resulting Sb 2 Te 3 films are characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray (EDX) and Auger spectroscopies. Moreover, the Seebeck coefficient of the Sb 2 Te 3 film deposited at 200°C is determined, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 67 publications
(66 reference statements)
3
25
1
Order By: Relevance
“…[192] The average Seebeck value (153.35 ± 6.68 µV/K) of the film deposited at 200 °C is higher than that of bulk Sb 2 Te 3 crystals but corresponds very well to values reported by Yan et al for Sb 2 Te 3 films consisting of much smaller Sb 2 Te 3 particles (100 nm diameter). [193] A similar Seebeck coefficient (65 µV/K) was found for Sb 2 Te 3 films which were deposited by coevaporation of elemental Sb and Te on glass substrates.…”
Section: Single Source Precursors Of the General Type M(er')supporting
confidence: 77%
See 1 more Smart Citation
“…[192] The average Seebeck value (153.35 ± 6.68 µV/K) of the film deposited at 200 °C is higher than that of bulk Sb 2 Te 3 crystals but corresponds very well to values reported by Yan et al for Sb 2 Te 3 films consisting of much smaller Sb 2 Te 3 particles (100 nm diameter). [193] A similar Seebeck coefficient (65 µV/K) was found for Sb 2 Te 3 films which were deposited by coevaporation of elemental Sb and Te on glass substrates.…”
Section: Single Source Precursors Of the General Type M(er')supporting
confidence: 77%
“…EDX studies also revealed the presence of small amounts of carbon (5-6%), which are rather located on the substrate surface due to incompletely decomposed precursor residues as was shown by scanning Auger electron microscopy studies (SAM/AES). [192] The powder diffractogram of the film deposited at 200 °C (Fig. 40a) proved the formation of pure, crystalline Sb 2 Te 3 films.…”
Section: Single Source Precursors Of the General Type M(er')mentioning
confidence: 97%
“…[16] In addition, Ph 2 SbTeEt [17] and MeSb(TeBu) 2 [18] were recently shown to be promising SSPs for the wet-chemical synthesis of Sb 2 Te 3 nanoparticles and the CVD deposition of Sb 2 Te 3 thin films. While early AACVD studies with Et 2 SbTeEt and Te(SbEt 2 ) 2 failed to give Sb 2 Te 3 films, [19] we successfully demonstrated the promising potential of Te(SbEt 2 ) 2 to serve as SSP for the solution based [20] and gas phase based [21] synthesis of highly stoichiometric Sb 2 Te 3 nanoparticles and thin films with high Seebeck coefficients. These studies clearly demonstrated that the formation of antisite defects in Sb 2 Te 3 nanoplates can be significantly reduced by use of this specific SSP.…”
Section: Introductionmentioning
confidence: 83%
“…However, we demonstrated in previous CVD studies that epitaxial Sb 2 Te 3 and Bi 2 Te 3 films were deposited on Al 2 O 3 substrates at higher temperatures of about 400 °C, [19] whereas the CVD deposition of a single source precursor (Et 2 Sb) 2 Te at low temperature (200 °C) only yielded polycrystalline Sb 2 Te 3 films. [20] Obviously, the substrate temperature plays a major role in CVD deposition and we think that this is also true for ALD processes. In order to prove the influence of the substrate temperature on the resulting film morphology, ALD deposition studies were performed at a higher substrate temperature (170 °C), which is in the optimal temperature range as reported by .…”
Section: Introductionmentioning
confidence: 97%